A randomized controlled trial to evaluate the effectiveness of different methods on pain management during orthodontic debonding - Sanjay Prasad Gupta; Shristi Rauniyar; Pravin Prasad; Pranil Man Singh Pradhan (SpringerOpen, 2022)
Abstract Background Orthodontic treatment procedures like separator placement, archwire placement, orthodontic force application, miniscrew placement and debonding procedure usually involve pain and discomfort. Pain perception and methods to reduce pain during debonding in regard to gender and different locations of oral cavity is still a poorly documented issue in orthodontics. The aim of this study was to evaluate the effectiveness of different methods on pain management during debonding and its association with gender and location. Materials and methods One hundred and forty orthodontic patients in the stage of debonding were randomly assigned into four groups according to different methods used during debonding; Group A: Medication group (Paracetamol given 1 h before debonding), Group B: Finger pressure group, Group C: Stress relief group and Group D: Control group. A visual analog scale (VAS) was used to assess the pain intensity just after debonding for each sextant. Results Among 140 participants, 61 (43.57%) were males and 79 (56.43%) were females. Differences in VAS score in different areas of oral cavity among all groups were found to be significant (p < 0.05). Total VAS score was greater in control group (16.67) followed by stress relief group (13.33) and finger pressure group (10) and least in medication group (8.33). The VAS score was higher in the upper front and lower front sextants in all the groups. Females reported higher VAS score and in upper front sextant, it showed significant difference (p = 0.018). On comparison, total VAS scores were statistically significant difference in medication-stress relief arm pair (p = 0.009), medication-control arm pair (p < 0.001) and finger pressure-control arm pair (0.002). The total VAS score comparison between medication-finger pressure arm was not significant (p = 0.172). Conclusions Pain perceived during debonding varies in different areas of oral cavity among all the groups. Anterior area of oral cavity and female seems to be more sensitive to pain. Use of finger pressure can be used effectively for pain management during debonding.